Profiling of bacterial assemblages in the marine cage farm environment, with implications on fish, human and ecosystem health - Kolda, Anamarija; Gavrilović, Ana; Jug-Dujaković, Jurica; Ljubešić, Zrinka; El-Matbouli, Mansour; Lillehaug, Atle; Lončarević, Semir; Perić, Lorena; Knežević, Dražen; Vukić Lušić, Darija; Kapetanović, Damir (Ecological indicators, 2020)
[Display omitted] •Bacterial composition significantly different in the seawater vs. sediment.•Rare taxa harbor aquaculture pathogens, e.g. Tenacibaculum, Vibrio, Pseudomonas.•Control sediments have more aerobic and facultatively anaerobic bacteria.•Functional groups for respiration of S compounds major in aquaculture sediments.•Biomarkers important for aquaculture management are identified. This research presents a comprehensive study of bacterial assemblages within the water column and in the surface sediments in the zone of two European sea bass cage farms. By the application of the high-throughput amplicon sequencing of 16S rRNA gene, and further implementing microbial ecology tools, a bacterial segment from cage culturing systems and their respective controls were analyzed, with special reference to potential impact on animal, human and environmental health. Samples of seawater and sediments were collected seasonally, at locations situated in the central and southern Adriatic Sea. Bacterial composition was significantly different in the seawater vs. sediment. No significant differences in alpha diversity in sediments were indicated between aquaculture and control sites, and it appears that it is not affected by farming practices. Control sediments have higher relative abundance of aerobic and facultative anaerobic bacteria, while aquaculture sediments are markedly anaerobic. Sediments largely contain functional groups for respiration of sulfate and sulfur compounds, though doubly more in aquaculture sites. Seasonal groupings of bacterial assemblages were confirmed in the seawater, with higher relative abundance of known aquaculture pathogens (except Photobacterium in the winter samples) detected in the winter and summer, opposed to other two seasons. Rare taxa were analyzed in the sediment and in the water column in the search for known fish pathogens, with five genera detected: Vibrio, Pseudomonas, Photobacterium, Tenacibaculum and Mycobacterium. Biomarkers important for the impact of aquaculture on the environment were identified, e.g. Blastopirullela, Sva0081, Suflurovum, Spirochaeta 2, etc., as well as human and fish potential pathogens: Vibrio ichtyoentery, V. harvey, Acinetobacter lwoffi, A. johnsonii, Clostridium perfringens, etc. Chemoheterotrophy has emerged as the dominant functional group in both environments. Regarding priorities for aquaculture microbial management, seawater seems to contain a higher percentage of taxa connected to health-related functional groups.